Propuesta de un procedimiento para evaluar el liderazgo estratégico en la empresa avícola granma, año 2012 - Soria Yánez, Mayra Carolina (2012)
This investigation was carried out in the Poultry Company Granma, belonging to the MINAGRI. In their introduction the foundations of the leadership are based in the mark of the strategy. The general objective of this investigation consists in: To propose a procedure for the evaluation of the leadership in the mark of the strategic address, of the directive of the Poultry Company Granma in their administration, sustaining as hypothesis the following one: If the leadership of the directive is evaluated, at the same time that it will allow to characterize it and to evaluate it, it will propitiate to conform a methodological proposal to form the leadership like support of the strategic address in the Poultry Company Granma….